Pesticide contamination of bird species from Doñana National Park (southwestern Spain): Temporal trends (1999–2021) and reproductive impacts. (15th April 2023) - Peris, A.; Baos, R.; Martínez, A.; Sergio, F.; Hiraldo, F.; Eljarrat, E.
Abstract: Doñana National Park (DNP) is a protected area renowned for hosting a wide variety of birds. However, the agricultural practices in its surroundings might cause pesticide contamination of the park biota. This work aimed to assess temporal trends of a wide variety of pesticides, including organochlorine (OCPs), organophosphate (OPPs) and pyrethroid (PYRs) pesticides, in bird eggs collected for more than twenty years (1999–2021) in DNP. Twenty-six pesticides were detected, being 4, 4′-DDE the most frequently detected and also the one with the highest concentrations (up to 2.55 μg g −1 ww), exceeding in some cases the values usually reported to cause detrimental health and reproductive effects in avian species. An overall decreasing trend of OCPs was observed. In contrast, an apparent increase in PYRs was detected from 2013 onwards, especially for fenvalerate, whose median concentration was 3–5 orders of magnitude higher in the most recent samples. Moreover, other pesticides such as oxadiazon, oxyfluorfen and fenitrothion were first detected in 2021 samples. Finally, two variables estimating the cumulative impact of pesticides significantly decreased the breeding performance of a top predator such as the booted eagle. Therefore, it is essential to control the use of pesticides in the agricultural practices surrounding DNP and to study their potential negative impact on the bird populations breeding in this protected area. Graphical abstract: Image 1 Highlights: Twenty-six pesticides detected, being 4, 4′-DDE the most frequent and with the highest levels. An overall decreasing trend of organochlorine pesticides was observed between 1999 and 2021. An apparent increase in pyrethroids was detected from 2013 onwards, particularly fenvalerate. Oxadiazon, oxyfluorfen and fenitrothion were first detected in 2021 samples. Pesticides' cumulative impact decreased the breeding performance of booted eagles.